Decision making for basketball clutch shots: A data driven approach - Eppel, Y.; Kaspi, M.; Painsky, A. (Journal of Sports Analytics, 2023)
Decision making is considered one of the most important aspects for winning a basketball game. In the final minutes of the game (clutch time), these decisions become even more crucial. In particular -who shall take the final, game-winning shots? While some coaches believe it is the team`s star, others may prefer the `clutch` player (who seemingly performs better in clutch time), or the `hot` player who was having a great game that night. In this work we study policy making in clutch minutes. Specifically, we introduce different policies for choosing the shot-taker (for example, according to field goal percentage). Then, we compare the policies and rank them to create a policy hierarchy, which serves as a decision guide for the coach. We show that when our recommendations are implemented (i.e., the highest ranked player takes the shot) the success rate is significantly greater: 51.2%, compared to 41.3% in commonly taken clutch shots. Furthermore, our results indicate that players who excelled in past clutch shots are more likely to succeed, independently to their performance in the current game.